Mixed Oxides Derived from Hydrotalcites Mg/Al Active in the Catalytic Transfer Hydrogenation of Furfural to Furfuryl Alcohol - López-Asensio, Raquel; Cecilia-Buenestado, Juan Antonio; Herrera-Delgado, María Concepción; Larrubia-Vargas, María Ángeles; García-Sancho, Cristina; Maireles-Torres, Pedro Jesús; Moreno-Tost, Ramón (IOAP-MDPI, 2022)
Herein, a family of Mg/Al hydrotalcites was synthesized as catalytic precursors of MgAlOx mixed oxides. Both hydrotalcites and mixed oxides were characterized and the mixed oxides were tested in the reduction of furfural to yield furfuryl alcohol by MPV reaction using isopropanol as hydrogen donor. Different catalytic parameters were tested, such as the type of alcohol, calcination temperature of the hydrotalcite, and reaction temperature. Furfural and isopropanol were adsorbed on the MgAl-3 catalyst to follow the species adsorbed on the catalyst by FTIR analysis. The results showed that the isopropanol was activated as isopropoxide and furfural changed the adsorption site with increasing temperature but maintaining the h1-conformation. The catalytic performances were associated with the basicity of the catalysts and the deactivation processes have been attributed to the existence of adsorbed species on the surface, mainly due to furfural-derived compounds. The catalysts were reused in three consecutive cycles showing a sharp drop of catalytic activity. To recover the activity, the catalysts were calcined at 500 °C but the activity was only partially recovered. The XPS analysis after reactivation showed that the catalyst surface was modified due to the segregation of hydroxides of Mg and Al.
Keywords: Espectroscopía; Hydrotalcite; MPV reaction; Furfural; Isopropanol; FTIR spectroscopy